An emerging innovative UV disinfection technology: virucide activity on SARS-CoV-2. (20th October 2021) - Messina, G; Della Camera, A; Ferraro, P; Amodeo, D; Falcone, V; Corazza, A; Nante, N; Cevenini, G
Abstract: Background: Surface sanitation is one of the key points to reduce the risk of transmission both in healthcare and other public spaces. UV-C is already used in hospital and laboratory's disinfection procedure furthermore some recent studies show effectiveness on SARS-CoV-2. UV-C may be generated by Lamps and Light Emitting Diode, but novel sources are emerging. The aim of the study was to test a device having UV chips for inactivating SARS-CoV2. Methods: The descriptive study was conducted in the period between June and July 2019, in laboratories of the University of Siena and of the scientific park of Toscana life sciences. The device, shaped in a rectangular box, contained six UV chips (10 mW each, with a peak at 264nm nm ranging from 260 to 350 nm) placed in the bottom. Central and short side long positions were tested expecting different dose levels. Each experiment was conducted in triplicate, with and without the device lid, at 3, 6 and 10 minutes. All repetitions were tested for SARS-CoV-2 having a virus suspension of 10^7.2. Results: The zones with the higher value of irradiance (max 187.9 µW/cm2) were near the corners of the box, while the lowest (min 61.9 µW/cm2) near one of the long sides. The light distribution was almost symmetrical. The tests revealed a viral charge reduction from an initial concentration of virus suspension of 10^7.2 TCID50/mL, of more than 99.9% after 3 minutes of UV exposure; at 6 minutes, the minimum Log10 attenuation value was over 5 Log10(99, 999%); the maximum detectable attenuation value of Log10 = 5.7 was measured at 10 minutes. Conclusions: This device is the first one which introduces this novel UV chip source, similarly it is the first time it was tested against the SARS-CoV-2. Objects that need to be disinfected may benefit of such devices according a proper exposition time for homogeneous disinfections of the surfaces. Key messages: Implementation of cleaning and disinfection devices has been shown to reduce Sars-cov-2 infection incidence. In the hospital sanitation field, but also in public places and homes, using viable alternatives as UV-C can contribute to the reduction of pandemic spread.